IoT-based Fishpond Monitoring to Improve Water Quality - Putri, Yuliana; Agnesia, Meidina (Politeknik Negeri Padang, 2025)
To address the issues of suboptimal water levels and the risk of pond water overflowing due to rainfall, a fish pond control and monitoring system utilizing Internet of Things (IoT) technology has been developed. The system monitors three primary parameters—water level, temperature, and rainfall—which are all controlled and observed through an internet-connected platform. This real-time monitoring, facilitated via a website, enables fish farmers to accurately and efficiently monitor the condition of their ponds. The system is built using a NodeMCU ESP8266 microcontroller, which is equipped with sensors to automatically collect data on the water level, temperature, and rainfall. This data is continuously updated and can be accessed online anytime, anywhere. As a result, fish farmers can quickly react to changes in pond conditions, such as adjusting water levels to prevent overflow, or maintaining optimal water temperature for fish health. The real-time feedback provided by the system also allows users to take timely actions to prevent issues that could negatively impact the fish’s health or overall pond productivity. This IoT-based fish pond monitoring and control system makes pond management more efficient and minimizes the risks posed by environmental factors such as sudden weather changes. Additionally, it helps optimize the overall productivity of fish farms by offering a reliable, automated solution that reduces the need for constant manual supervision. This leads to better management of fish ponds and enhances productivity